2016
DOI: 10.3390/ijms17101724
|View full text |Cite
|
Sign up to set email alerts
|

UBXD Proteins: A Family of Proteins with Diverse Functions in Cancer

Abstract: The UBXD family is a diverse group of UBX (ubiquitin-regulatory X) domain-containing proteins in mammalian cells. Members of this family contain a UBX domain typically located at the carboxyl-terminal of the protein. In contrast to the UBX domain shared by all members of UBXD family, the amino-terminal domains are diverse and appear to carry out different roles in a subcellular localization-dependent manner. UBXD proteins are principally associated with the endoplasmic reticulum (ER), where they positively or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 137 publications
1
16
0
Order By: Relevance
“…The presence of the ubiquitin-regulatory X (UBX) domain, particularly in combination with the ubiquitin-associated (UBA) domain, allows selective members of the UBXD family to mediate ubiquitination and proteasomal degradation of diverse substrates as part of the ER-associated degradation (ERAD) mechanism or independent of ERAD (Lee et al, 2013;Park et al, 2016;Rezvani, 2016;Song et al, 2005). For our next step, we decided to determine whether UBXN2A can facilitate/enhance CHIP-dependent ubiquitination of mot-2.…”
Section: Ubxn2a Promotes Ubiquitination Of Mot-2 In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the ubiquitin-regulatory X (UBX) domain, particularly in combination with the ubiquitin-associated (UBA) domain, allows selective members of the UBXD family to mediate ubiquitination and proteasomal degradation of diverse substrates as part of the ER-associated degradation (ERAD) mechanism or independent of ERAD (Lee et al, 2013;Park et al, 2016;Rezvani, 2016;Song et al, 2005). For our next step, we decided to determine whether UBXN2A can facilitate/enhance CHIP-dependent ubiquitination of mot-2.…”
Section: Ubxn2a Promotes Ubiquitination Of Mot-2 In Vitromentioning
confidence: 99%
“…Our previous findings showed that a UBX (ubiquitin‐regulatory X) domain‐containing protein (Rezvani, ) called UBXN2A binds and inhibits mot‐2, resulting in the induction of apoptosis and reduction in cell proliferation in both in vitro and in vivo models (Abdullah et al ., ; Sane et al ., ). UBXN2A binds to the substrate‐binding domain of mot‐2 and interferes with mot‐2's protein interaction networks (Sane et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The largest family of regulatory cofactors is the Ubiquitin Regulatory X (UBX) domain containing protein family, which has thirteen members in human and eleven in D. discoideum ( Alexandru et al, 2008 ; Rijal et al, 2016 ). All members possess the eponymous, highly conserved UBX domain in their C-terminal region, which adopts a ubiquitin-like fold and is critical for the interaction with the N domain of p97 ( Rezvani, 2016 ). Five of the D. discoideum UBXD family members, among them UBX domain containing protein 9 (UBXD9), are orthologs of human UBXD proteins ( Rijal et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Proteins such as UBXD1 to UBXD6, UBXD9 and UBXD11 contain only a UBX domain. The UBA (ubiquitin associated)-UBX cofactors, such as UBXD7, UBXD8 (FAF2), UBXD10 (p47), UBXD12 (FAF1) and UBXD13 also accommodate an UBA domain that is fundamental for interacting with ubiquitinated substrates 16 , 33 . Cofactors such as p47 harbor, in addition to the UBX and UBA domains important for their function in the UPS, a SHP (BS1, binding segment 1) motif as another site for interaction with the Nc subdomain of VCP 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%